DA'WAH IN THE DIGITAL ERA FROM THE PERSPECTIVE OF QUR'ANIC AND HADITH INTERPRETATION SCHOLARS - Muhammad Thoriq Nurul Ihsan (Indonesian Journal of Islamic Communication, 2022)
This study examines legal perspectives on da'wah in the digital era, where nearly everyone has access to advanced communication tools. In today's digital age, spreading Islamic teachings as a form of da'wah has become significantly easier, particularly through the use of digital platforms such as Facebook, YouTube, and other social media channels. These platforms offer new opportunities for da'wah by allowing content to be disseminated quickly and widely. One common method is through video sharing, which enables viewers to watch religious messages in a visual format, making the delivery more engaging and accessible. Additionally, written content distributed online, such as articles or posts, can also serve as effective tools in delivering Islamic messages. From a legal and religious standpoint, utilizing these digital mediums for da'wah is permissible, as long as the content aligns with Islamic values and serves the purpose of guiding others towards goodness and truth. This new form of digital da'wah can be seen as a bridge between traditional Islamic preaching and modern technology, making religious messages more relevant and reachable to contemporary audiences across diverse backgrounds.